Sosialisasi Kendalikan Jarimu Saring Dulu Baru Sharing Kepada Ibu-Ibu PKK Desa Karangduren - Tri Yulianti; Purwono, Purwono; Monica Puspa Dewi (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
The rapid development of technology has affected all areas of life, including the field of information. With the internet, disseminating information is easy and fast. In addition, the existence of social media has created a new habit of sharing posts or news to other netizens. However, this ease of information dissemination does not always have a positive impact on society. This is due to the lack of information literacy skills of the community which is the cause of a lot of information that is not clear the truth is spread widely quickly. One effort that can be a solution to this problem is the formation of a new culture, namely S filter first, then share. This culture can be formed by increasing awareness within each individual, and the main step is to hold socialization.